Lifetime Interpersonal Polyvictimization: Abuse Typologies and Mental Health Outcomes in a Nationally Representative Sample of Men from the United States - Burns, Carol Rhonda; Armour, Cherie (International Journal of Population Data Science, 2018)
Background Interpersonal polyvictimisation experiences are a specific type of traumatic experience that include physical, sexual or psychological attacks against a person and much research has concentrated on female only or mixed samples. Being a victim of one form of victimisation experience increases the risk of further victimisation experience resulting in polyvictimisation, and elevates the likelihood on negative mental health outcomes. Objectives The current study seeks to establish interpersonal polyvictimisation typologies within a male sub-population of a large epidemiologic sample and establish associated risk of psychopathology across a range of mental health outcomes. Methods Using data from 15,794 adult males, aged over 18 years who completed the NESARC III, a Latent Class Analysis (LCA) of the endorsement of interpersonal victimisation experiences was conducted to establish latent profiles of interpersonal polyvictimisation. Subsequently regression analysis was conducted to establish risk of psychopathology across a series of DSM 5 diagnosed mental health conditions. Findings A three-class solution was deemed optimal in line with published fit statistics. Class 3 was categorised by low/no endorsement and was labelled ‘normative’, Class 2 was categorised by high endorsement of childhood indicators and was labelled ‘childhood’, class 1 showed a moderate endorsement across life-course victimisation indicators and was labelled ‘lifecourse’. Interpersonal polyvictimisation profiles showed increased risk of negative mental health outcomes in adulthood suggesting that distinct typologies of interpersonal polyvictimisation exist within the adult male only population. Conclusions Experiences of interpersonal polyvictimisation are robustly associated with adult psychopathology in males including elevated rates of the likelihood of PTSD, Anxiety and Depression in a dose response fashion. Interventions and support services should therefore be developed and implemented that are targeted to gender specific distinctiveness.